2018
DOI: 10.1055/a-0625-6440
|View full text |Cite
|
Sign up to set email alerts
|

A novel endoscopic ultrasound-guided through-the-needle microbiopsy procedure improves diagnosis of pancreatic cystic lesions

Abstract: EUS-guided microbiopsy procedure was technically feasible, with a high diagnostic yield. Further prospective studies are needed to confirm these promising results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 10 publications
5
46
1
Order By: Relevance
“…Endoscopic ultrasound‐guided (EUS) fine needle aspiration with assessment of cytological material has served as a cornerstone in the evaluation of these lesions, although the cytological material is often scarce. Recently, a novel through‐the‐needle microbiopsy forceps has been developed (Moray™; US Endoscopy, Mentor, OH, USA), which enables clinicians to obtain microbiopsies (MBs) from the cyst wall under EUS guidance, as described in a previous publication . Mutations in genes regulating cell cycle and repair appear to occur early in the natural history of mucinous cysts, and may serve as diagnostic markers for a pre‐operative estimate of malignant potential .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic ultrasound‐guided (EUS) fine needle aspiration with assessment of cytological material has served as a cornerstone in the evaluation of these lesions, although the cytological material is often scarce. Recently, a novel through‐the‐needle microbiopsy forceps has been developed (Moray™; US Endoscopy, Mentor, OH, USA), which enables clinicians to obtain microbiopsies (MBs) from the cyst wall under EUS guidance, as described in a previous publication . Mutations in genes regulating cell cycle and repair appear to occur early in the natural history of mucinous cysts, and may serve as diagnostic markers for a pre‐operative estimate of malignant potential .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel through-the-needle microbiopsy forceps has been developed (Moray TM ; US Endoscopy, Mentor, OH, USA), which enables clinicians to obtain microbiopsies (MBs) from the cyst wall under EUS guidance, as described in a previous publication. 3 Mutations in genes regulating cell cycle and repair appear to occur early in the natural history of mucinous cysts, and may serve as diagnostic markers for a pre-operative estimate of malignant potential. 4 The aim of this study was to present our experience with next-generation sequencing (NGS) of MBs from pancreatic cysts.…”
Section: Introductionmentioning
confidence: 99%
“…Charlotte Vestrup Rift 1 Anders Toxvaerd 2 Bojan Kovacevic 3 Pia Klausen 3 Carsten Palnaes Hansen 4 Peter Vilmann 3 Jane Preuss Hasselby 1…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Recently, several studies reported the utility of EUSthrough-the-needle biopsy (EUS-TTNB) for the diagnosis and risk stratification of the malignancy of pancreatic cystic lesions. [42][43][44][45][46] This novel technique enables direct sampling from the walls of pancreatic cystic lesions using biopsy microforceps through an EUS-FNA needle. One multicenter study enrolling 56 patients reported that technical success was 100% and the rate of adequate sampling for histological diagnosis was 83.9%.…”
Section: Endoscopic Ultrasound-through-the-needle Biopsymentioning
confidence: 99%
“…44 The rate of adverse events was 16.1%, but these were mild and were resolved by conservative therapy. Kovacevic et al 45 carried out EUS-TTNB in 31 consecutive patients with pancreatic cystic lesions and reported that clinical management was changed in six out of the 31 (19.4%) patients as a result of this evaluation. In some cases, the diagnosis could not be obtained using EUS-TTNB but could be obtained by cytology or cyst fluid evaluation; therefore, it may be important to diagnose using not just one but both of these methods together.…”
Section: Endoscopic Ultrasound-through-the-needle Biopsymentioning
confidence: 99%